Cultural Heritage and Traditional Practices of Kanchipuram: An Analytical Study - Sarala Devi, T (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2026)
Kanchipuram occupies a distinguished position in the cultural landscape of South India due to its continuous association with religion, art, architecture, and traditional craftsmanship. The city is widely recognized for its ancient temples, ritual practices, festivals, and the globally renowned silk handloom tradition. This study analyzes the cultural heritage and traditional practices of Kanchipuram by examining both tangible and intangible cultural elements. Using secondary sources and an analytical approach, the paper explores how religious institutions, occupational traditions, and community participation have contributed to cultural continuity. The study finds that, despite the pressures of modernization and socio-economic change, Kanchipuram has retained its cultural identity through adaptive preservation of traditions. The paper emphasizes the need for heritage conservation strategies and policy support to sustain these practices for future generations.